Measurement of isolated-photon pair production in pp collisions at s√=7 TeV with the ATLAS detector - Onofre, A. (2013)
The ATLAS experiment at the LHC has measured the production cross section of events with two isolated photons in the final state, in proton-proton collisions at √ s = 7 TeV. The full data set collected in 2011, corresponding to an integrated luminosity of 4.9 fb−1 , is used. The amount of background, from hadronic jets and isolated electrons, is estimated with data-driven techniques and subtracted. The total cross section, for two isolated photons with transverse energies above 25 GeV and 22 GeV respectively, in the acceptance of the electromagnetic calorimeter (|η| < 1.37 and 1.52 < |η| < 2.37) and with an angular separation ∆R > 0.4, is 44.0 +3.2 −4.2 pb. The differential cross sections as a function of the di-photon invariant mass, transverse momentum, azimuthal separation, and cosine of the polar angle of the largest transverse energy photon in the Collins-Soper di-photon rest frame are also measured. The results are compared to the prediction of leading-order parton-shower and next-to-leading-order and next-to-next-to-leading-order parton-level generators.